THE USING ARTIFICIAL INTELLIGENCE IN THE METHODOLOGY OF PEDAGOGICAL RESEARCH ORGANIZATION BY STUDENTS OF HIGHER EDUCATION - Volianiuk, Анастасія (Journal of Information Technologies in Education (ITE), 2025)
The article is dedicated to analyzing the possibilities of using AI in the methodology and technologies of organizing pedagogical research, determining effective ways of its integration to improve the effectiveness of the research process, and summarizing the risks of using AI in order to minimize them. The current state of research on this problem is considered, emphasizing the lack of attention to the methodological aspect of AI integration into pedagogical science. Key research questions are defined: the use of AI by students in writing scientific papers and organizing research, effective ways of using AI in pedagogical research, and preventing excessive/incorrect use. The role of the teacher in the information age and the potential of AI as a powerful tool in scientific research are considered. The article analyzes the challenges associated with the use of AI in organizing pedagogical research, such as data quality, complexity of result interpretation, ethical issues, and risks of academic dishonesty. The necessity of expert verification of AI-generated results and adherence to the regulatory framework governing its use is emphasized. The experience of AI integration into the educational component «Methodology and Technology of Organizing Pedagogical Research. Educational Measurements» at the Faculty of Pedagogy of Kherson State University is described. A survey of students regarding their interaction with AI was conducted, revealing problems they encounter during AI interaction, such as incorrect queries, excessive use of AI, lack of dialogue with AI, and risks of academic dishonesty. Based on surveys and practical tasks, it was established that AI is most often used at the stages of topic formulation, information retrieval, and text editing. Recommendations for the effective use of AI in the methodology and technologies of organizing pedagogical research are provided. The article proposes principles of interaction with AI, such as the formation of ethical norms, the development of critical thinking, and the use of AI as an auxiliary tool. The main problems of AI use and ways to minimize them are systematized in a table, which considers risks such as academic dishonesty, plagiarism, low data quality, ethical issues, lack of critical thinking, the «black box» problem, data confidentiality, simplification of the research process, and data bias. Corresponding minimization methods are proposed for each risk. The article also presents recommendations for using AI at various stages of organizing pedagogical research, from topic formulation to dissemination of results. It is emphasized that AI can be a useful tool at every stage, increasing work efficiency and helping to avoid routine tasks. The necessity of further research in this area, the development of practical recommendations, and the implementation of interdisciplinary approaches to develop research competencies of pedagogical specialties students are emphasized.